Intelligent Technologies for Interactive Entertainment 4th International ICST Conference, INTETAIN 2011, Genova, Italy, May 25-27, 2011, Revised Selected Papers - Camurri, Antonio; Costa, Cristina; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the proceedings of the 4th International Conference on Intelligent Technologies for Interactive Entertainment (INTETAIN 11). The 20 full papers, 3 posters, 10 demos and 4 workshops presented were carefully selected from numerous submissions. The conference aims enhancing the understanding of recent and anticipated advances in interactive technologies, and their applications to entertainment, education, culture, and the arts. Interaction technologies are having relevant changes in the last years, and will influence the way users consume and interact with the media and applications, both locally and over the Internet. The explosion of natural, multimodal, and touch based interfaces, and their access to the general public, has made new interaction paradigms a reality.
Keywords: Computer science; Computer graphics; Computer vision; Optical pattern recognition; Information systems; Computer Science; User Interfaces and Human Computer Interaction; Media Design; Computer Graphics; Computer Appl. in Arts and Humanities; Image Processing and Computer Vision; Pattern Recognition